Analisis Kompetensi Kepribadian Guru PAI Dalam Memberikan Keteladanan Moral pada Siswa di SMP Swasta Bangun Mulia Pangkalan Berandan - Marhan Hasibuan; Azhar Azhar (PKP Pusat Jurnal LPPM IAi Nasional Laaroiba, 2021)
The level of competence has practical implications for human resource planning, the level of competence for knowledge and expertise tends to be more pronounced as one of the characteristics of humans, while attitudes, character traits and competency motives are more hidden and are at the central point of one's personality. Personality is a dynamic organization within an individual consisting of psycho-physical systems that determine the unique way of adapting the individual to his environment. Good or bad morals, depending on the conscience and character of each individual. There is a significant influence between the Personality Competency Analysis of PAI teachers in describing the moral exemplary of Bangun Mulia Pangkalan Berandan. A steady and stable personality with essential indicators, namely showing the ability to act as a professional teacher, he has consistency in acting as a professional teacher, has consistency in acting in accordance with the norms that apply in life. As a teacher, he must have a disciplined and wise person. This is important, because we still often see and hear students whose behavior is inappropriate and even contrary to good moral attitudes. must have a mature personality because sometimes many educational problems arise due to the lack of maturity of a teacher. Authorized Personality A teacher must have a behavior that has a positive effect on students. Able to operate computers and also focus on supporting good learning. In other words, Islamic education teachers are not technologically illiterate.